Anesthesia for combined off-pump coronary artery bypass grafting with radical nephrectomy and inferior vena cava tumor excision extending to the right atrium: A case report - Koshy, Kuzhithattil Aniyan; Pradeep, Kizakke K (Indian Journal of Case Reports, 2025)
This case report describes the successful anesthesia management of a 60-year-old male with renal cell carcinoma extending into the inferior vena cava (IVC) and right atrium (RA). Utilizing transesophageal echocardiography for real-time monitoring and cardiopulmonary bypass with deep hypothermia and selective antegrade cerebral perfusion, a multidisciplinary team achieved complete tumor resection. The patient’s complex medical history included type 2 diabetes, hypertension, and coronary artery disease, necessitating concurrent coronary artery bypass grafting (CABG). The surgical approach included IVC and RA tumor excision and careful perioperative management to address significant blood loss, potential thromboembolism, and post-operative complications such as atrial fibrillation, low cardiac output, and hepatic dysfunction. This case underscores the importance of advanced intraoperative monitoring and a collaborative, multidisciplinary approach in managing concomitant CABG and renal cell carcinoma with intracardiac extension, achieving a successful outcome despite the high complexity and risk.